A trophic model to simulate the combined affect of artisanal and recreational fisheries on a Mediterranean ecosystem : - Albouy, Camille (2009)
Marine Protected Areas (MPAs) have the potential to enhance the long-term sustainability of coastal resources upon which artisanal fisheries depend. However, recreational fisheries (spear, boat and shore fishing), which are expanding in coastal zones world-wide, may weaken the benefit of MPAs towards artisanal fisheries which are declining. This phenomenon is common is the Mediterranean Sea despite the establishment and the reinforcement of more than 100 MPAs in the last decades. Here we used the Bonifacio Straits Natural Reserve (BSNR) as a case study to simulate the combined effects of various levels of artisanal and recreational fishery efforts on coastal resources and ecosystem functioning. The BSNR ecosystem was modelled using mass-balance equations of trophic interactions (Ecopath model). The model encompassed 32 trophic groups, including detritus, primary producers, the main species of pelagic, demersal and benthic invertebrate fish and non fish vertebrates. We defined two fleets (artisanal and recreational) for which we simulated various combinations of fishing efforts during 20 years using Ecosim, including a total collapse of the artisanal fishery, a total prohibition of recreational activities, a fourfold increase in these two fishing activities. We demonstrated that both fishing activities have a synergistic top down effect on the food web and decrease the biomass of targeted groups such as piscivorous species. We also found non trivial patterns of biomass variations that emerge for some groups when the two fishing activities produce unexpected trophic cascades. Our trophic approach revealed that some species groups may provide negative signals of biomass decrease when MPAs are set or reinforced due to a combined effect of artisanal and recreational fisheries. Overall, our results illustrate the need to rely on modelling tools to manage MPAs and to anticipate ecosystem level consequences of socio-political decisions that aim to sustain coastal resources facing artisanal and recreational fisheries.